Enhancing the nutritional value of sweet pepper through sustainable fertilization management - Stoleru, Vasile; Mangalagiu, Ionel; Amăriucăi-Mantu, Dorina; Teliban, Gabriel-Ciprian; Cojocaru, Alexandru; Rusu, Oana-Raluca; Burducea, Marian; Mihalache, Gabriela; Rosca, Mihaela; Caruso, Gianluca; Sekara, Agnieszka; Jităreanu, Gerard (Frontiers in Nutrition, 2023)
The need for healthy foods has become a major concern in our modern world, as the global population continues to grow and environmental challenges intensify. In response to these challenges, researchers have started to explore a range of sustainable solutions, including organic farming practices, precision agriculture, and the development and testing of innovative biofertilizers. Consistent with these ideas come the aim of this study which set out to compare the effect of three different types of new fertilizers (Nutrifine® - chemical, Orgevit® - organic chicken manure and Micoseed® - biological with microorganisms) and two sweet pepper varieties, Blancina F1 and Brillant F1, for which there is little information, on fruit production, proximate analysis, phytonutrient content, phytochemical composition, and mineral content. The results showed that the biological and organic fertilizations had a significant positive impact on most of the parameters analyzed, starting with yield and continuing with acidity, phytonutrient content (total phenolic content, lycopene, β-carotene), antioxidant activity and phytochemical composition (chlorogenic acid, p-coumaric acid, quercetin and isoquercetin). Only in the case of mineral content, the chemical treatment gave better results compared with the organic and biological fertilizers. Overall, this study provides valuable information on the potential of organic and biological fertilizers to enhance the nutritional value of sweet peppers from Blancina F1 and Brillant F1 cultivars, paving the way for subsequent research aimed at achieving superior quality and increased yields.